Pelatihan Pembuatan Lilin Aroma Terapi Pada Ibu-Ibu Anggota PKK Gabahan Rt. 05 Rw. 12 Jombor Sukoharjo - Hanik, Nur Rokhimah; Firtiani, Rindi Diah Ayu; Cahyani, Fiky Ariska (Jurnal Gema Ngabdi, 2024)
Most of the women from PKK Gabahan RT 05 work as housewives who need to acquire skills that can increase their family income. They have never received counseling or training on making Aromatherapy Candles from universities or other institutions. From the results of the interviews, several residents wanted counseling and training on making aromatherapy candles which could be used as an alternative to therapeutic drugs and could also increase financial income. For this reason, the biology education study program Abdimas Team will provide training to PKK Gabahan RT mothers. 05 Rw. 15 Jombor about making Aromatherapy Candles. They want counseling on this theme because most people don't understand how to make Aromatherapy Candles. The objectives of the community service are to provide education on how to make Aromatherapy Candles. Training is carried out once. The method used is lecture and question and answer, as well as practical guidance on how to make Aromatherapy Candles. The target of this counseling and training is to increase understanding of how to make Aromatherapy Candles among mothers who are members of the PKK Gabahan RT. 05 Rw. 12 Jombor by 20%. From the results of the training in making Aromatherapy Candles among women members of the PKK Gabahan hamlet RT 05 RW 12 Jombor, it can be concluded that there has been an increase in understanding of the process of making Aromatherapy Candles from an average score of 39.28 to 81.63, meaning there has been an increase in understanding of 39.28 to 81.63. 42.34 (112.52 %). The results of Aroma Therapy Candles can be used by mothers as health therapy medicines for their own needs or can also be sold to increase family income.